1991
DOI: 10.1038/clpt.1991.65
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of intravenous indomethacin in neonates with symptomatic patent ductus arteriosus

Abstract: The population pharmacokinetics of intravenous indomethacin were investigated with 665 indomethacin serum concentrations from 83 neonates (mean +/- SD: gestational age, 28.8 +/- 2.5 weeks; postnatal age, 5.7 +/- 4.7 days; birth weight, 1.13 +/- 0.40 kg) receiving indomethacin for symptomatic patent ductus arteriosus. A one-compartment open model was used for pharmacokinetic analysis. Hypotheses were tested to determine which developmental and demographic data influenced clearance (CL) and volume of distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 0 publications
3
9
0
1
Order By: Relevance
“…Individual estimates for V in our population are in good agreement with those from previous studies [9, 10, 12, 13]. Each of our infants with a PNA ≥ 30 days ( n = 5) had an estimated V > 0.34 l kg −1 , which is above the lower limit of the reported range in adults (0.34–1.57 l kg −1 ) [27].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Individual estimates for V in our population are in good agreement with those from previous studies [9, 10, 12, 13]. Each of our infants with a PNA ≥ 30 days ( n = 5) had an estimated V > 0.34 l kg −1 , which is above the lower limit of the reported range in adults (0.34–1.57 l kg −1 ) [27].…”
Section: Discussionsupporting
confidence: 89%
“…Since then its use in the treatment of clinically significant PDA has been widely documented, but the response to treatment has been extremely variable [7][8][9][10][11]. Studies of indometacin in the newborn have also reported considerable interindividual variability in its pharmacokinetics [9,10,[12][13][14][15][16]. Traditional pharmacokinetic studies are difficult to perform in infants because of the need for multiple blood samples, which creates ethical and technical problems.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of data on the pharmacokinetics of many drugs in neonates and children is related to blood sampling limitations for this population. One way around this problem is to collect a few samples from many individuals and analyze the data by means of a population-based approach (7,10,13,14,29,34,51,54). The administration of aminoglycosides once daily has been shown to be as well tolerated as or better tolerated than the conventional schedules (twice daily or thrice daily) in adults and children.…”
mentioning
confidence: 99%
“…A utilização da IM para o tratamento farmacológico do fecho do CA em recém-nascidos foi descrita pela primeira vez em 1976 (Vert et al, 1980;Wiest et al, 1991), sendo hoje um dos fármacos de eleição efetivo e apropriado, induzindo o fecho do CA em mais de 80% dos recém-nascidos prematuros, quando administrado por via intravenosa (Angerio, Kot, 1998;Archer, 1993;Baptista et al, 1999;Bhatt, Nahata, 1989;Grosfeld et al, 1996;Hammerman, 1995).…”
Section: Indometacina Como Fármaco De Escolha No Tratamento Farmacolóunclassified